Pengaruh Komitmen Profesional, Locus Of Control, Dan Sosialisasi Antisipatif Mahasiswa Terhadap Whistleblowing: - Winda Devila Zalmi; Efrizal Syofyan; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to analyze empirically the effect of professional commitment, locus of control and anticipatory socialization of accounting students on whistleblowing. The type of this research is quantitative research, the population in this study were students of the 2014 and 2015 primary years at the Padang State University. The sample was chosen as many as 100 respondents, the data used in this study were primary data derived from questionnaires distributed to respondents. This study uses multiple regression analysis using SPSS 21 software.The results of this study indicate that professional commitment variables have a significant positive effetc on whistleblowing, internal locus of control variables have a significant positive effect on whistleblowing, external locus of control variables have a significant negative effect on whistleblowing and anticipatory socialization variable of accounting students has no significant effect on whistleblowing. The fourth hypothesis is rejected.